Vertical Integration in Tradable Green Certificate Markets - Jessica Coria; Jūratė Jaraitė (Center for Economic Studies and ifo Institute (CESifo), 2024)
This study examines how the impact of Tradable Green Certificates (TGC) on profitability and investment behavior varies depending on the vertical integration status of regulated firms. Our theoretical model predicts that vertical integration does not lead to higher profits when internal pricing aligns with market values for green certificates. However, it stimulates greater investment in renewable electric capacity since it reduces the costs of the sourced certificates. Empirical analysis of the Swedish TGC system confirms these findings, revealing that vertically integrated firms did not experience profit increases. Instead, they exhibited distinct investment patterns, prioritizing cost-effective technologies like hydro and thermal capacity over more expensive renewables, in contrast to non-integrated firms.
Keywords: L10; L50; Q58; 330; renewable energy; tradable green certificates; vertical integration; firm-level data; causal effects; profits; investments; Sweden